Peningkatan Kompetensi Guru Dalam Mendesain Pembelajaran Melalui Model Pelatihan Pembelajaran Kreatif: Indonesia - Aswad (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2022)
This research of this study is to increase the competence of teachers in designing learning through a creative training model. The subjects of this study were Islamic religious education teachers in the target area of the Ministry of Religious Affairs of Pekanbaru City, totaling 32 people. The study consisted of two cycles. For this action research to succeed well without obstacles that interfere with the smooth running of the research, the researcher compiles the stages passed in class action research, namely: 1) planning, 2) implementation of actions, 3) observation and reflection. The data from the study were collected using observation and questionnaires. Furthermore, the data is analyzed quantitatively and qualitatively. The results showed the results that there was an increase in teacher competence in designing learning after being given training through creative learning training, namely an increase in competence from 72.37% to 77.34% there was an increase of 5%, from before training (Initial data) and after coaching by supervisors up to (Cycle II) 72.37% to 77.34% and from (cycle I) to (cycle II) also an increase of 77.34 % - 87.19 % = 9.84 %, The average competence of teachers to design learning through creative learning training before being given an improvement of 59.38% rose to 100%.